Special drawing rights and development : an inquiry into the monetary aspects of a link between special drawing rights and development finance - Haan, Roelf L. (Leiden : Stenfert Kroese, 1971)
This study deals mainly with the monetary aspects of the problems involved in international development financing on which it offers some personal views as a contribution as regards special drawing account.
Issued also as thesis--Vrije Universiteit, Amsterdam.
Includes bibliographical references: p. [171]-175.
usc 16/08/2018
Loans
Keywords: Special drawing rights; International finance